Simultaneous quantification of TB-500 and its metabolites in in-vitro experiments and rats by UHPLC-Q-Exactive orbitrap MS/MS and their screening by wound healing activities in-vitro - Rahaman, Khandoker Asiqur; Muresan, Anca Raluca; Min, Ho phil; SON, Jung hyun; Han, Hyung-Seop; Kang, Min-Jung; KWON, Oh-Seung (Elsevier BV, 2024)
Background TB-500 (Ac-LKKTETQ), derived from the active site of thymosin β4 (Tβ4), has various biological functions in its unacetylated form, LKKTETQ. These functions include actin binding, dermal wound healing, angiogenesis, and skin repair. The biological effects of TB-500, however, have not been documented. And the analysis of TB-500 and its metabolites have been neither simultaneously quantified nor structurally identified using synthesized authentic standards. Methods This study was aimed to investigating simultaneous analytical methods of TB-500 and its metabolites in in-vitro and urine samples by using UHPLC-Q-Exactive orbitrap MS, and to comparing the biological activity of its metabolites with the parent TB-500. The metabolism of TB-500 was investigated in human serum, various in-vitro enzyme systems, and urine samples from rats treated with TB-500, and their biological activities measured by cytotoxicity and wound healing experiments were also evaluated in fibroblasts. Results The simultaneous analytical method for TB-500 and its metabolites was developed and validated. The study found that Ac-LK was the primary metabolite with the highest concentration in rats at 0？6 h intervals. Also, the metabolite Ac-LKK was a long-term metabolite of TB-500 detected up to 72 hr. No cytotoxicity of the parent and its metabolites was found. Ac-LKKTE only showed a significant wound healing activity compared to the control. Conclusion The study provides a valuable tool for quantifying TB-500 and its metabolites, contributing to the understanding of metabolism and potential therapeutic applications. Our results also suggest that the previously reported wound-healing activity of TB-500 in literature may be due to its metabolite Ac-LKKTE rather than the parent form.